The Pregnancy care and baby parenting patterns in toraja ethnics - Hartati Bahar; Karlina Powatu (CORE JOURNAL, 2022)
One of the causes of the high maternal mortality rate in Indonesia is the limited knowledge of the community and the existence of cultural influences. This study aims to analyze in depth the pattern of maternity care and infant care patterns in the Toraja ethnicity in the working area of ​​the Mekar Public Health Center, Kendari City. The type of research used is qualitative research with a phenomenological approach. The results showed that the pattern of maternity care and baby care in terms of elemental assessment in the Toraja tribe, namely the behavior that was more recommended, namely moving a lot, light exercise and walking; abstained behavior is not allowed to cut nails, cut hair, bathe after 4 pm, not allowed to sit at the door, not allowed to put a towel around his neck; preferred foods are katuk leaves and nuts; The foods that are abstained are bananas, pineapples, and durians, spicy foods and coconut milk. In terms of the prescriptive elements in the Toraja tribe, namely pregnancy checks, infant feeding, namely breastfeeding and complementary feeding such as red flour porridge, Ambon banana and mixed porridge after 6 months and over, and massage therapy. In terms of cognitive elements, the Toraja tribe has trust during pregnancy, but in terms of baby care, they have certain trust in baby caretakers in terms of views about the placenta, namely aluk ma'lolo. Therefore, education with a local culture approach can still be carried out as long as safe for mother and children